A primer on the Canadian bankers' acceptance market - Kaetlynd McRae; Danny Auger (Bank of Canada, 2018)
This paper discusses how the bankers' acceptance (BA) market in Canada is organized and its essential link to the Canadian Dollar Offered Rate (CDOR). Globally, BAs are a niche product used only in a limited number of jurisdictions. In Canada, BAs provide a key source of funding for small and medium-sized corporate borrowers that may not otherwise have direct access to the primary funding market because of their size and credit ratings. More recently, BAs have also become an increasingly important funding source for large corporate borrowers because of credit-rating downgrades in certain sectors and industry consolidation. With the market's continued growth, BAs account for the greatest portion of money market instruments issued by non-government entities and are the second-largest money market instrument overall in Canada, averaging just over 25 per cent of the total domestic money market in 2017. For the investment community in Canada, BAs provide a source of short-term income and liquidity because of their relatively attractive yield, liquidity and credit ratings. The BA market is intrinsically linked to CDOR, which was originally developed to establish a daily benchmark reference rate for BA borrowings. This rate is quite nuanced compared with rates in other jurisdictions in that it is not directly a bank borrowing rate. Instead, it is a committed lending rate at which banks are contractually willing to lend cash to corporate borrowers with existing BA facilities. CDOR is also used as the main interest rate benchmark for calculating the floating-rate component of both over-the-counter and exchange-traded Canadian-dollar derivative products. Another use of CDOR is to determine interest payments on floating-rate notes.
Keywords: G; G1; G18; G2; G21; G23; 330; Financial institutions; Financial markets; Financial system regulation and policies; Market structure and pricing